Análise dos padrões de prescrição de analgésicos e anti-inflamatórios não esteroides dos cirurgiões- dentistas do estado de Minas Gerais que atuaram no Sistema Único de Saúde - Alex Júnio Silva da Cruz (2020)
The aim of this study was to analyze the prescription patterns of nonsteroidal anti-inflammatory drugs, opioids and analgesics by dental practitioners at the Brazilian National Health System in the State of Minas Gerais in 2017. This is an ecological study that analyzed data from the Integrated Pharmaceutical Care Management System. The discharged drugs were gathered by the Anatomical Therapeutic Chemical Classification System and, the number of Defined Daily Doses (DDD) was estimated for each municipality. The dependent variable was the number of DDD per 1,000 inhabitants per year. The independent variables included socioeconomic and oral healthcare service characteristics from the municipalities- GINI index, Human Development Index, Bolsa Família program coverage per 1,000 inhabitants, percentage of rural population, dental practitioners in the Brazilian National Health System per 1,000 inhabitants, first dental appointment coverage, oral health teams modality 1 and 2 per 1,000 inhabitants and, percentage of individual clinical procedures. Descriptive and analytics statistical analysis of data was developed using SPSS software version 25.0. In 2017, 70,747 dental prescriptions of medicines to manage pain and inflammation were processed in 375 municipalities. Ibuprofen presented the highest frequency of dispensing (34.88%; n= 24,676). The average number of DDD per 1,000 inhabitants per year per municipality for non-steroidal anti-inflammatory drugs, opioids and analgesics was 91.159 (Standard Deviation [SD]= 130.105), 5.414 (SD= 10.759) and 23.879 (SD= 36.604), respectively. Among the variables tested, dental practitioners in the Brazilian National Health System per 1,000 inhabitants (p <0.001), first dental appointment coverage (p= 0.010), Bolsa Família program coverage per 1,000 inhabitants (p= 0.022), oral health teams modality 1 and 2 per 1,000 inhabitants (p= 0.022) and the percentage of rural population (p= 0.014) were associated with the prescription of anti-inflammatory drugs. Regarding analgesics, first dental appointment coverage (p= 0.002) and the Bolsa Família program coverage per 1,000 inhabitants (p= 0.012) were positively associated with the outcome. These findings suggest there are regional differences in the prescription of anti-inflammatory drugs and analgesics in Minas Gerais related to social and organizational characteristics of the oral healthcare services.